2016
DOI: 10.17795/jhealthscope-30203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Net Epoxy Resin for Electromagnetic Shielding in X-Band Frequency Range

Abstract: Background: X-band microwaves, which are part of electromagnetic waves, have various applications, such as satellite communications, radar, navigation, air traffic control, marine functions, and weather stations. Therefore, many workers are exposed to these waves in the workplace. Previous studies showed that these frequencies have adverse health effects. In occupational health, the use of shielding as an engineering measure is a priority in controlling radiation in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Zaroushani et al . reported the EMI SE in the X‐band frequency range for neat epoxy network cured with polyamido amine imidozolium but the value was low for the samples with 2 mm thickness (around 1.9 dB) …”
Section: Resultsmentioning
confidence: 99%
“…Zaroushani et al . reported the EMI SE in the X‐band frequency range for neat epoxy network cured with polyamido amine imidozolium but the value was low for the samples with 2 mm thickness (around 1.9 dB) …”
Section: Resultsmentioning
confidence: 99%
“…The problem of protection against high energy microwaves EM radiation is typical due to high intensity reciprocal interference of electronic instruments working in close proximity [1][2][3][4][5][6]. Furthermore, uncontrolled long-term exposure to these radiations imposes hazardous consequences on living organism creating potential health risk even jeopardizing their life [7]. Electromagnetic shielding is probably best option to mitigate the hazardous effect of unwanted microwave radiation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies related to the effect of number of layers on EMSE conducted by researchers confirm that the EMSE increases with an increase in the number of conductive fabric layers [1][2][3][4][5][6][7][8][9]. Prerumalraj et al 2009 [13] produced copper core yarns to make twill and plain-woven fabrics, it was observed that, the EMSE of double layered fabrics in both weave configurations increases in comparison with their single layer variants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have also been many electromag-netic compatibility studies on nanocomposites for electromagnetic shielding (10)(11)(12)(13)(14)(15)(16)(17). In electromagnetic shield topics, the selection of suitable shields is an important and interesting subject for experts in this field.…”
Section: Introductionmentioning
confidence: 99%